ANALYSIS OF KEY COMPETITIVE STRATEGIES EMPLOYED BY INTERNATIONAL COMPANIES (International Journal of Innovative Technologies in Economy, 2018)
Today there are plenty of companies that compete for customers’ attention and loyalty. But some companies are successful and win in this battle, and others are being disappeared from markets. The reason of this is a successful or failing competitive strategy. There are a lot of factors that cause this choice and define its results. In the article there is provided a theoretical ground of types and key features of competitive strategies. It is proved with examples of companies that use them and the way they do it. There is also given an analysis of key factors that make these strategies and companies in general successful.